1978
DOI: 10.1136/hrt.40.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Coronary thrombosis in pathogenesis of acute myocardial infarction. Histopathological study of coronary arteries in 108 necropsied cases using serial section.

Abstract: An extensive histopathological study was carried out on the hearts of 108 patients with electrocardiographically proven acute myocardial infarction dying after admission to a coronary care unit. The occluded or the narrowest segments of the coronary arteries were examined at intervals of 100 mu using serial sections. Serial sectioning is important in such a study because the pathology of the lumen can vary considerably within a 2 to 3 mm segment. A high incidence (80.3%) of thrombus formation corresponding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(34 citation statements)
references
References 23 publications
2
31
0
1
Order By: Relevance
“…19 In 64%-100% of patients with nonoperative MIs, coronary artery plaque fissuring occurs, 20,21 and in 65%-95% there is an acute luminal thrombus. [21][22][23][24][25] The pathophysiology underlying MIs in the operative setting is less clear.…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…19 In 64%-100% of patients with nonoperative MIs, coronary artery plaque fissuring occurs, 20,21 and in 65%-95% there is an acute luminal thrombus. [21][22][23][24][25] The pathophysiology underlying MIs in the operative setting is less clear.…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…[1][2][3][4] Postmortem studies show an association between large atherosclerotic plaques and acute coronary syndromes. [28][29][30][31] On the other hand, some angiographic studies report that acute coronary syndromes may arise from lesions with < 50% stenosis. [32][33][34] If the culprit lesion of the acute coronary syndrome is larger, but associated with more positive remodeling, this may in part reconcile the discrepancies between the pathologic and angiographic findings of patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Our rationale begins with the fact that, in autopsy studies of victims of fatal MI, a second occlusive thrombus is found in 6% to 16% of victims, though most of these individuals have a second vulnerable plaque (rarely three). 25,26 Approximately half of these have rupture or erosion with a mural (non-infarctrelated) thrombus. In patients with stable symptoms, arterial inflammation is not diffuse, and in these patients most plaques are predominantly fibrotic.…”
Section: Clinico-pathological Correlationmentioning
confidence: 99%